Religion and the Theories of Science: A Response to Barbour - Russell, Robert J. (Zygon, 1996)
Abstract. This paper offers a detailed response to “Religion and the Theories of Science” in Barbour's Gifford Lectures I. Topics include: complementarity, indeterminacy, parts and wholes, and Bell's theorem in quantum theory; metaphysical issues raised by relativity theory and thermodynamics, principally the problem of temporality and “top-down” versus “bottom—up” causality; design arguments and the origins of the universe in astronomy and creation; and God's action in the context of evolution and continuing creation. Areas of agreement and disagreement between Barbour and myself over philosophical and theological implications are presented, and endnotes indicate further areas of conversation.